Markers of excessive exercise - McKenzie, D. C. (Canadian Journal of Applied Physiology, 1999)
There is no single biological marker that is diagnostic of an overtrained state; however, several parameters deserve further study. The time to volitional fatigue on a cycle ergometer at an intensity of 110% of the individual anaerobic threshold represents a possible laboratory test. Salivary IgA holds promise as a useful immunological marker of the overtrained state and further research is needed to determine the validity of plasma glutamine as a blood marker.